The physics of the squat - Evangelista, P.; Aberti, G. (EWF Scientific Magazine, 2016)
The squat is used both in athletic training and rehabilitation programmes, therefore - although it is not an actual contest - the Sports Science graduate will have to face this exercise sooner or later. He/she will be surprised to find totally heterogeneous case studies: some individuals squat right to the ground, as if they were born to make this movement, whereas others will have to make significant effort to achieve a sufficiently correct movement. In fact, when dealing with the "squat problem", it should not be underestimated that it is considered a multifactorial movement. There are some factors that determine the qualitatively correct execution of any movement. First and foremost are the anthropometric characteristics, namely our own size, that naturally cannot but affect what we do. For example: a short person is at a disadvantage when playing basketball, because height is not a trainable characteristic and it affects many aspects of a movement. Having said that, one may argue that this is a reductive vision because, in reality, all the shapes of our body, not only height, are decisive factors: in addition to the total length, there is also the "shape" of the individual elements that determines the length of the levers, therefore the ability to move. In other words, if the insertion of a muscle is more or less displaced with respect to the centre of rotation, the lever will be more or less disadvantageous or, if the femoral neck is angled in a certain way, or the pelvis has a certain conformation, it will be possible to flex the femur on the pelvis to a greater or lesser extent, and consequently squat more or less. Next comes joint mobility: the ability of a joint to move the articular segments with a greater or lesser angular excursion depends on the ligamentous apparatus, the tendons and the connective tissue bands surrounding the joint. For example, the lack of ankle dorsiflexion constitutes an extremely critical element for the execution of a squat. In addition, the ability to generate muscular strength and to stabilise a joint. In brief: joint stability is the ability - while performing a given movement - to "lock" a joint in a certain position and not move it. Lastly, the mental representation of oneself during the movement, deriving from proprioceptive signals, such as, for example, the information on joint opening, muscle and tendon tension, and from exteroceptive signals such as the head position, vision, etc. All these inputs result in a perception of movement and combine to create the executive motor pattern. The final result derives from a series of elements in which it is difficult to determine which is the most critical. What is certain, however, is that a movement should be analyzed in its entirety, including how the individual elements contribute to the realisation of the whole. In literature, there is a multitude of test protocols on the squat movement that highlight not only the individual's ability to perform the movement effectively and safely, but also to identify critical elements. It is precisely because movement depends on some characteristics which are fixed and on others that are highly adaptable, that these tests can be used not only for an initial assessment at the start of the movement training programme, but also during the programme, in order to monitor improvements and any other points worthy of attention. In this article, we will attempt to explain how anthropometric measurements may influence movement, creating, in fact, facilitating or limiting conditions for the success of the same. The text presents some concepts that are considered difficult, often rightly so, and also unnecessary, often wrongly so: such as kinetic chains and the centre of mass. Understanding these two concepts will allow us to critically discuss two of the many "myths" of the squat: the "child squat" and the "knees behind the toes squat."